PEMBERDAYAAN PEREMPUAN DESA BERBASIS INOVASI PERTANIAN ORGANIK UNTUK PENGUATAN EKONOMI KELUARGA DAN KETAHANAN PANGAN - Sarman, Rohmat; Sari, Lira Mustika; Suryaman, Restu Akbar (Universitas Muhammadiyah Mataram, 2026)
Abstrak:.Program pengabdian ini bertujuan memperkuat ekonomi keluarga dan ketahanan pangan melalui pemberdayaan perempuan desa berbasis inovasi pertanian organik. Mitra adalah Kelompok Wanita Tani (KWT) Silih Asih di Kabupaten Karawang yang menghadapi rendahnya pemanfaatan pekarangan dan ketergantungan pada pupuk kimia. Metode mengintegrasikan penyuluhan, pelatihan teknologi tepat guna (ember tumpuk untuk kompos/pupuk cair serta budidaya polybag–vertikultur), pendampingan lapangan, dan penguatan kelembagaan kelompok. Kegiatan melibatkan 50 peserta selama delapan bulan. Evaluasi melalui observasi serta kuesioner pre–post menunjukkan peningkatan pengetahuan rata-rata 55 poin dan keterampilan praktik pembuatan pupuk organik 68 poin. Sebanyak 70% rumah tangga memanfaatkan pekarangan untuk sayuran/TOGA dan menghemat belanja pangan sekitar 25% per bulan. Penerapan ember tumpuk juga menurunkan volume sampah organik rumah tangga sekitar 40%, serta 85% peserta menyatakan komitmen melanjutkan praktik secara mandiri. Dampak sosial-ekonomi diperkuat melalui pembentukan tiga kelompok usaha perempuan untuk produksi pupuk organik, pengolahan hasil panen, dan pemasaran lokal. Program ini meningkatkan hardskill (kompos/pupuk cair, budidaya pekarangan, perawatan tanaman) serta softskill (kolaborasi, manajemen kelompok, kewirausahaan sederhana) dan layak direplikasi pada desa sejenis.Abstract: This community service program aims to strengthen household economic resilience and food security through the empowerment of rural women based on organic agricultural innovation. The partner group was the Kelompok Wanita Tani (KWT) Silih Asih in Karawang Regency, which faced limited utilization of home yards and high dependence on chemical fertilizers. The implementation integrated counseling, appropriate technology training (the ember tumpuk system for compost and liquid organic fertilizer production, as well as polybag–vertical gardening), field mentoring, and group institutional strengthening. The program involved 50 participants over eight months. Evaluation using observation and pre–post questionnaires indicated an average increase of 55 points in knowledge and a 68-point improvement in practical skills related to organic fertilizer production. Approximately 70% of households utilized their home yards to grow vegetables and medicinal plants, resulting in an average reduction of household food expenditure of about 25% per month. The application of the ember tumpuk system also reduced household organic waste by approximately 40%, and 85% of participants expressed commitment to continuing the practices independently. Socio-economic impacts were further reinforced through the establishment of three women’s business groups focused on organic fertilizer production, post-harvest processing, and local marketing. Overall, the program enhanced both hard skills (composting/liquid fertilizer production, home-yard cultivation, and plant maintenance) and soft skills (collaboration, group management, and basic entrepreneurship) and is considered replicable in similar rural contexts.